2019
DOI: 10.1038/s41590-019-0352-y
|View full text |Cite
|
Sign up to set email alerts
|

The lung environment controls alveolar macrophage metabolism and responsiveness in type 2 inflammation

Abstract: IL-4)) activation, linked to wound repair and type 2 pathology 3, 4, 5. Although pulmonary macrophage sub-populations inhabit dramatically different anatomical sites, such as the airways and tissue parenchyma, it is not yet clear how location influences their ability to respond to type 2 inflammation. In particular, reports of M(IL-4) marker expression on lung macrophages during type 2 inflammation 6, 7, 8, 9 have involved experimental approaches that may not clearly distinguish macrophages from other myeloid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
144
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 157 publications
(167 citation statements)
references
References 58 publications
11
144
0
3
Order By: Relevance
“…lung Mres) displayed muted M(IL-4) activation profiles compared to Mmono during Nippostrongylus brasiliensis infection [18]. Furthermore, this discrepancy was linked to different metabolic programs in Mres as compared to Mmono [18]. Similar differences in metabolism linked to an altered response profile of alveolar macrophages have also been observed in a model of acute lung inflammation and injury [19].…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…lung Mres) displayed muted M(IL-4) activation profiles compared to Mmono during Nippostrongylus brasiliensis infection [18]. Furthermore, this discrepancy was linked to different metabolic programs in Mres as compared to Mmono [18]. Similar differences in metabolism linked to an altered response profile of alveolar macrophages have also been observed in a model of acute lung inflammation and injury [19].…”
mentioning
confidence: 85%
“…This is not limited to the liver, as it has been recently demonstrated that alveolar macrophages (i.e. lung Mres) displayed muted M(IL‐4) activation profiles compared to Mmono during Nippostrongylus brasiliensis infection . Furthermore, this discrepancy was linked to different metabolic programs in Mres as compared to Mmono .…”
mentioning
confidence: 95%
“…In type 2 cellular immune responses, such as allergy or helminth infection, IL-4 production results in the polarization of macrophages resulting in a distinct phenotype M(IL-4) characterised by the expression of arginase-1 as well as factors involved in tissue repair, and antiinflammatory mediators [14]. Using markers recently described [2,15,16], and highly specific, gating strategy to differentiate IMs and AMs, Svedberg et al [13], observed that AMs were less responsive than IMs in vivo, following systemic or local administration of IL-4. AM hyporesponsiveness to IL-4 was confirmed in mice infected with the rodent helminth Nippostrongylus brasiliensis, which elicits the potent production Immunometabolism.…”
mentioning
confidence: 99%
“…https://doi.org/10.20900/immunometab20200007 Immunometabolism 3 of 8 of IL-13 and IL-4 in the lung resulting in the activation of M(IL-4) that facilitate tissue repair and provide protection against reinfection [17,18]. Svedberg et al [13], report that AMs, contrary to IMs, fail to expand or express typical markers of M(IL-4) following infection. The differential responsiveness of AM and IM to available IL-4 could result from the distinct ontogeny or environmental niche of these cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation